Bioinformatics Analysis Identifies p53 as a Candidate Prognostic Biomarker for Neuropathic Pain - Gao, Yibo; Sun, Na; Wang, Lieju; Wu, Ying; Ma, Longfei; Hong, Juncong; Ren, Jinxuan; Zhu, Bin; Yu, Lina; Yan, Min (Frontiers in Genetics, 2018)
Neuropathic pain(NP) is a is a kind of chronic pain that different to the common type of pain, in fact, the mechanisms of NP are still poorly understood. Explore the genetic changes and various neurobiological in NP could provide important diagnosis and treatment tools for the clinician. GSE24982 is a mRNA microarray dataset, and we downloaded it from the Gene Expression Omnibus database to identify key genes in NP. Differentially expressed genes(DEGs) were obtained using BRB-ArrayTools software and R. Functional and pathway enrichment analysis of DEGs were performed using Metascape online. Protein–protein interaction network was created by STRING and visualized by Cytoscape. A total of 668 DEGs were obtained, and Tp53 showed the highest nodule levels in all of these genes, so we tested and verified that in chronic constriction injury(CCI) model. Our results showed that overly expressed p53 genes, and caspase-3 subsequent increase in dorsal root ganglia neurons, increased apoptotic changes in the dorsal root ganglion may be partly responsible for the development of CCI induced NP.